Integrity, Religiosity, Gender: Factors Preventing on Academic Fraud - Nurlita Novianti (Association of Certified Fraud Examiners Indonesia Chapter, 2021)
The purpose of this study is to explain and predict the effect of respondent integrity and religiosity in relation to the possibility of academic fraud, which is mostly done by students. The study was also supposed to look at the effect of gender on students’ academic fraud behavior. This study involved 102 accounting students from public universities in Malang, Indonesia. Researchers used survey methods to collect data, and data were analyzed by SPSS software using multiple linear regression and moderated regression analysis. The findings of this study indicate that a lack of integrity and religion has a negative impact on the likelihood of academic fraud. This shows that students with higher levels of honesty and religion are less likely to commit academic fraud. While gender did not appear to have a substantial impact on the effect between integrity, religiosity, and the likelihood of academic cheating, both male and female students had similar levels of integrity and religiosity. The findings of this study will be useful for universities in formulating academic policies related to academic fraud prevention measures.